KNOWLEDGE, ATTITUDES, AND PREPARATION FOR IMPLEMENTING ELECTRONIC PRESCRIPTIONS AMONG PROFESSIONAL IN CHARGE AT RETAIL PHARMACIES IN HO CHI MINH CITY (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the proportion of pharmacy managers with adequate knowledge, attitudes, and preparedness for implementing electronic prescriptions in Cu Chi district (formerly), Ho Chi Minh city, in 2025.Methods: A cross-sectional descriptive study with analysis was conducted among 208 pharmacy managers at retail drug outlets. Data were collected using a questionnaire and analyzed with descriptive statistics.Results: Among 208 participants, 79.8% demonstrated good knowledge, and 76.9% had positive attitudes toward electronic prescribing. However, only 52.9% showed adequate preparedness, while 47.1% were not adequately prepared.Conclusion: Pharmacy managers exhibited relatively good knowledge and positive attitudes; however, preparedness and implementation remain limited. Strengthening training and technical support is recommended to improve the effectiveness of electronic prescribing in retail pharmacy settings.
Keywords: Knowledge, attitude, preparation, electronic prescription.